Autotrophic Denitrification with Sulfide as Electron Donor: Effect of Zeolite, Organic Matter and Temperature in Batch and Continuous Uasb Reactors - Huilinir-Curio, C; Montalvo-Martinez, S (Elsevier Ltd, 2016)
The effect of zeolite and temperature on the autotrophic denitrification process for hydrogen sulfide removal in the presence of organic matter was evaluated. Four batch reactors (1 l) at 35 °C were used to study the effect of zeolite on denitrification, without the presence of organic matter. Two continuous UASB reactors (6 l) were used for the autotrophic denitrification with addition of natural zeolites at mesophilic controlled temperature (35 °C) and room temperature (13-20 °C). In continuous assays, COD/N ratios between 1.4 and 10 were used. It was found that zeolites have a positive effect on the autotrophic denitrification startup process (batch and continuous modes), decreasing by up to 50% the time required to achieve stabilization conditions of the process. Autotrophic denitrification with zeolite as amendment in a continuous UASB in the presence of organic matter could be carried out at uncontrolled room temperatures (13 °C - 20 °C), although processes at a controlled mesophilic temperature of 35 °C were more efficient than the room temperature process. The proposed system allows the simultaneous heterotrophic-autotrophic denitrification, with removal percentages better than 95% for nitrogen and COD, while sulfide had removal percentages better than 75%. © 2015 Elsevier Ltd.